Automatic press dough machine using blnyk IoT - Murthy, Kirthiga; Waeleh, Nazreen; Che Azman, Muhammad Aliff Ikhwan; Sumardi, Antony; Mohd Chachuli, Siti Amaniah; Shamsudin, Nur Hazahsha; Zainuddin, Nooraini (Wydawnictwo SIGMA-NOT, 2023)
The food business is still lacking in several aspects in this blooming era of digitization, where practically every industry is heading towards industrial revolution 4.0. One of these is using manual dough presses, which still require people. This work aims to develop a prototype of an automatic press dough machine using a 3D printer with the addition of Blynk IoT. This prototype is designed to assist in evenly flattening a piece of dough to the necessary thickness without manpower. This system consists of NodeMCU, a motor driver, and a Wi-Fi module. NodeMCU and the motor driver are used to control the machine. In addition, the prototype can be operated remotely using the BLYNK app, which remotely uses a handphone. The prototype is able to produce three different dough thicknesses: 5, 10, and 15 mm. With the development of this system, it can be applied to various pastries, such as pizza, biscuits, and curry puffs, which employ dough as a significant component.